Q-switched Nd: Yag laser: Rhytid improvement by non-ablative dermal remodeling - D. J. Goldberg (2018)
BACKGROUND: The Q-switched Nd:YAG laser has been used for a variety of dermatologic indications including tattoo and hair removal, as well as vascular and pigmented lesion treatment. Previous studies have suggested that this laser may also be safe and effective in the non-ablative treatment of rhytids. OBJECTIVES: The purpose of this study was to evaluate the safety and efficacy of the Q-switched Nd:YAG laser in the non-ablative dermal remodeling of facial rhytids. METHODS: Eight subjects were treated at 3 monthly intervals with a Q- switched Nd:YAG laser. Two passes with fluences of 7J/cm2and a 3-mm spot size were utilized. Clinical improvement and adverse effects were assessed 3 months after the last treatment. RESULTS: Six of the eight subjects showed clinical improvement as assessed by an independent observer. No pigmentary changes, erythema, or scarring were observed at the end of the study. CONCLUSION: The Q-switched Nd:YAG laser may be used for the non-ablative treatment of facial rhytids.